Nanoscale LiZnN - luminescent half-Heusler quantum dots - Carter-Searjeant, S; Fairclough, SM; Haigh, SJ; Zou, Y; Curry, RJ; Taylor, PN; Huang, C; Fleck, R; Machado, P; Kirkland, AI; Green, MA (American Chemical Society, 2023)
Colloidal semiconductor quantum dots are a well-established technology, with numerous materials available either commercially or through the vast body of literature. The prevalent materials are cadmium-based and are unlikely to find general acceptance in most applications. While the III-V family of materials is a likely substitute, issues remain about its long-term suitability, and other earth-abundant materials are being explored. In this report, we highlight a nanoscale half-Heusler semiconductor, LiZnN, composed of readily available elements as a potential alternative system to luminescent II-VI and III-V nanoparticle quantum dots.